2002
DOI: 10.1046/j.1528-1157.2002.23801.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of an Educational Treatment Program for Patients with Epilepsy (MOSES): Results of a Controlled, Randomized Study

Abstract: Summary:Purpose: To evaluate the efficacy of the educational program MOSES (Modular Service Package Epilepsy). It was developed to improve patients' knowledge and understanding about their epilepsy, its treatment, and psychosocial consequences. The program intends to improve patients' coping with the disease, to strengthen self-esteem, and to support patients to become experts in managing their epilepsy.Methods: A controlled, randomized study design was used to examine the efficacy of MOSES. Patients from 22 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
172
5
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(191 citation statements)
references
References 22 publications
(41 reference statements)
10
172
5
4
Order By: Relevance
“…In addition, the results of the present study revealed that, satisfactory knowledge about epilepsy among studied caregivers was improved from more than quarter to more than three quarter after nursing intervention. This finding is congruent with study conducted in Germany by (May &Pfafflin, 2002). Who studied the efficacy of an educational treatment program for patients with epilepsy.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the results of the present study revealed that, satisfactory knowledge about epilepsy among studied caregivers was improved from more than quarter to more than three quarter after nursing intervention. This finding is congruent with study conducted in Germany by (May &Pfafflin, 2002). Who studied the efficacy of an educational treatment program for patients with epilepsy.…”
Section: Discussionsupporting
confidence: 89%
“…PWE who have developed efficient coping techniques, have high self-worth and foster more positive attitudes towards their condition are at less risk of psychosocial dysfunction [41,[99][100][101][102][103]. Therefore interventions that focus on increasing self-worth, developing effective coping strategies and positive cognition will help the individual accept their diagnosis, reduce psychosocial deficits and ultimately enhance quality of life.…”
Section: Strategies To Enhance Quality Of Lifementioning
confidence: 99%
“…In response to possible perceptions, it is important to educate teachers and school psychologists regarding epilepsy in children and the variability and diversity of seizure types and outcomes. Previous work educating patients and families [20] has found significant improvement in patient knowledge and family dynamics. In addition, it has been found that a neuropsychological report increases access to educational services for children with epilepsy in need of educational interventions [21].…”
Section: Significancementioning
confidence: 99%